THE STATE OF VASCULAR COMPONENT IN HEMODYNAMICS OF CHILDREN WITH MYOCARDIAL PATHOLOGY - Rak, L.I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
Hemodynamic interrelationships and functional state of vascular epithelium have been studied in children with myocardial pathology. The endothelial function was estimated by the tests with brachial arthery occlusion and with nitroglycerin. It has been established that in patients with myocardial pathology the pumping and contractile functions of the heart go down, and in 50 per cent of patients an insufficient endothelium related dilatation of vessels has been registered. The character of endothelial function in peripheric vessels depends upon the condition of general hemodynamics in children with myocardial pathology.